Elder Abuse and Its Association with Mental Well-Being and The Associated Sociodemographic Factors - A Community Based Cross-Sectional Study in Bengaluru, India - Archana Mandal; Mangala Subramanian; Srivatsa Srirama Reddy; Nagaraj Goud (Medsci Publications, 2023)
Background: Elderly abuse in form of neglect and disrespect has been an important risk factor affecting the mental well-being of elderly. This study estimated prevalence of elderly abuse, its association with their mental well-being and associated sociodemographic factors. Aims/Objectives: To determine the prevalence of the Elderly abuse in the Study area and to find the association of elderly abuse with mental well-being and sociodemographic factors Methodology: A cross-sectional study was conducted among 355 elderly persons in the field practice area of Vydehi Institute of Medical Sciences and Research Centre, Bengaluru from January 2020 to June 2021. The data was summarized as frequencies, proportions and association using regression. Results: The prevalence of elderly abuse was 18.3%. Abuse in elderly participants was associated with poor mental well-being, Odds Ratio (OR) 4.56 (95%CI,2.05-10.16) and among elderly with Risk of depression with AOR 5.72(95%CI,3.09-10.59). Abuse in all forms was significantly associated with poor mental well-being (p <0.001), presence of skeletal deformity and lack of physical activity (less than 30 minutes). Conclusions: The prevalence of elderly abuse is 18.3% in the study area and it is associated with poor mental well-being, higher risk of depression, and lack of physical activity.